ANALISIS EMPATI SISWA ETNIS MELAYU DAN EMPATI ETNIS JAWADI SMP NEGERI 3 PUJUD KECAMATAN PUJUD TAHUN PELAJARAN 2013 / 2014 - Yusuf, Sardi Yusuf Sardi; Yakub, Elni Yakub Elni; ', Asrona (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract The study is titled : “ The Analysis of the students’ malay emphatic ethnic and java emphatic ethnic at SMP Negeri 3 Pujud, Pujud district in academic year 2013 / 2014 ”. The problems of this study are : 1. How is the students’ emphatic level at SMP Negeri 3 Pujud, Pujud district in academic 2013 / 2014 ? and 2. How is the level of the students’ malay emphatic ethnic and java emphatic ethnic at SMP Negeri 3 Pujud, Pujud district in academic year 2013 / 2014 ?. Research objectives are : 1. To know the description of the students’ emphatic level at SMP Negeri 3 Pujud, Pujud district in academic year 2013 / 2014. And 2. To know the level of the students’ malay emphatic ethnic and java emphatic ethnic at SMP Negeri 3 Pujud, Pujud district in academic year 2013 / 2014. This research is focus on descriptive study. The population of this research is all the students’ malay ethnic and java ethnic, where the sample of this reseach by using total sampling. It means the population becomes sample. The result of this research are : 1. Emphatic of the students’ malay ethnic in the level underlying is 53 %,  47 % in the level surface feeling, and irrelevant hurful in the level 0 %. 2. Emphatic of the students’ java ethnic in the level underlying is 66 %,  34 % in the level surface feeling, and irrelevant hurful in the level 0 %. Based on the analysis above, it can be concluded as follow : 1. Both of the students’ malay ethnic and java ethnic have full attention to understand others peoples and 2. Both of the students’ malay ethnic and java ethnic have optimal emphatic. It means that the emphatic is suitable with the expectation. Key words : Emphatic, Ethnic, and Student